Menumbuhkan Motivasi Usaha Tawes Crispy pada Rumah Tangga Nelayan melalui Pelatihan dan Pendampingan Kelompok - Ratri Virianita; Kesha Jonathan; Nadia Putri Firdausa; Husnul Maab; Anzari Nurulia; Naurah Khansa; Khanya Pangestika; Indah Pratiwi Anhar (Institut Pertanian Bogor, 2020)
Tawes (Barbonymus gonionotus) is top local potential in Wonogiri District, especially in Watupecah Hamlet, Gedong Village, Ngadirojo Subdistrict. The low marketability and storability of tawes requires innovation in fish processing of tawes into tawes crispy chips (taspy) to increase the marketability of tawes which then be a business oppurtunity for fishermen households to increase their income. However, inovation itself is not enough to increase fishermen household income, it requires effort to build business motivation in fishermen households to take business opportunity. This community service program aimed to know the success of training and group mentoring as an effort to foster business motivation of fishermen households. The program was carried out using intensive training and group mentoring methods for 33 fishermen households in Watupecah Hamlet covering the development of business motivation, time and behavior management, processing and marketing of taspy products. The results of the program showed that there was a changed in fishermen's knowledge and motivation on the aspect of innovation, dreams, and financial management. The success of this program is evidenced by the growth of the business motivation of fishermen households based on data analysis before and after the implementation of the program. It can be concluded that training and group mentoring are effective techniques in fostering business motivation of fishermen households. Through training and group mentoring the fishermen had chance to dialogue, share suggestion and opinions, cooperate, and interact positively with each other in a comfortable atmosphere as to support the growth of stronger ebusiness motivation of fishermen households.